Response of the Photosynthesis and Antioxidant Systems to High-Temperature Stress in Euonymus japonicus Seedlings - Song-Heng Jin; Xue-Qin Li; Bing-Song Zheng; Jun-Gang Wang (Forest Science, 2010)
To uncover the adaptive mechanisms of photosynthesis under high temperatures (HTs), changes in the activity of ribulose-1,5-bisphosphate carboxylase/oxygenase (rubisco), the photosynthetic electron transport system, and antioxidant system were examined in a subtropical forest tree seedling, Euonymus japonicus. Compared with the control, the activity of rubisco and the quantum yield of photosystem (PS) II electron transport (ΦPSII) decreased in HT-treated seedlings, whereas energy-dependent quenching of chlorophyll (Chl) fluorescence (qE) increased. An analysis of the redox change of P700 and the oxygen uptake by PSI indicated that the cyclic electron transport around PSI operated at high rates in E. japonicus seedlings exposed to HT conditions. Furthermore, the levels of reactive oxygen species (ROS), the activities of superoxide dismutase, and the activities of ascorbate peroxidase were increased in HT-treated seedlings. Therefore, it is likely that an enzyme-based water-water cycle was initiated in E. japonicus seedlings in response to HT stress and that the HT-induced ROS might play an important function in HT conditions. Enhancement of cyclic electron transport around PSI and water-water cycles might help maintain a transthylakoid energy potential under HT conditions. This coordinated defense may play an important role in adaptation of E. japonicus cells to HT.